2013
DOI: 10.1111/jocn.12159
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a nurse‐led intensive educational programme on chronic kidney failure patients with hyperphosphataemia: randomised controlled trial

Abstract: Chronic kidney failure patients with hyperphosphataemia are more likely to benefit from nurse-led intensive educational programmes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
73
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(75 citation statements)
references
References 24 publications
1
73
0
1
Order By: Relevance
“…The effectiveness of a nurse-led educational intervention was also demonstrated by a recent study by Shi et al (2013) that sought to determine the effect of an educational intervention on the knowledge of phosphorus and the management of hyperphosphatemia in patients with CKD. In that study, the knowledge score of the experimental group increased significantly (F= 207.44, p < 0.001) vs. (F= 37.98, p < 0.001) in the control group post nurse-led educational intervention.…”
Section: Nurse-led Educational Intervention and Phosphate Binder Usementioning
confidence: 99%
See 3 more Smart Citations
“…The effectiveness of a nurse-led educational intervention was also demonstrated by a recent study by Shi et al (2013) that sought to determine the effect of an educational intervention on the knowledge of phosphorus and the management of hyperphosphatemia in patients with CKD. In that study, the knowledge score of the experimental group increased significantly (F= 207.44, p < 0.001) vs. (F= 37.98, p < 0.001) in the control group post nurse-led educational intervention.…”
Section: Nurse-led Educational Intervention and Phosphate Binder Usementioning
confidence: 99%
“…Educating patients on dietary phosphorus control is especially important in light of studies such as Cupisti et al, (2010) which showed that phosphorus knowledge of hemodialysis patients is low in comparison to their knowledge of other nutrients such as protein and potassium. Furthermore various studies continue to show that due to the significant consequences of hyperphosphatemia, individualized and ongoing patient education is necessary to decrease this abnormality and its associated high mortality risk in hemodialysis patients (Shi et al, 2013;Satoh et al, 2009;Sandlin, Bennet, Ockerby & Corradini, 2013, Baldwin, 2013.…”
Section: Individualized Educational Interventionmentioning
confidence: 99%
See 2 more Smart Citations
“…First, NEMO was implemented within the national health care setting, rather than operating in the idealized experimental environment, consequently generating "real life" useful and practical data [57]. Second, few specific exclusion criteria were applied, and the participants shared characteristics common to hyperphosphatemic hemodialysis patients reported from other areas of the world [7,[58][59][60][61][62][63]. These factors suggest that the results of this study are likely to be generalizable to this patient population.…”
Section: Randomized Controlled Trialmentioning
confidence: 99%